STUDY OF THE GRAPH ANALYTIC METHOD OF DETERMINING THE WORKING MODE OF A PUMP DEVICE FOR REDUCING THE MINE FROM GROUNDWATER - A. I. Nishonov1., U. T. Toshtemirov2 (Galaxy International Interdisciplinary Research Journal, 2023)
This in the article n on finding and using reserves to increase the operational efficiency of basic equipment, determine the level of regulation of pump operation modes, as well as reduce energy and material costs for their operation in mining enterprises data given.